Aging, Image and Appearance: the experience of the elderlies from UnATI EACH-USP, Brazil - Silva, Natália Polo (2013)
Raising perceptions of the elderlies regarding the appearance and images of seniors found on the internet and the effects on self-perception. Orientation of the ethnographic method. The category of analysis was found exaltation of youth versus denial of aging. We conclude that the dichotomous perception of images, which do not correspond to reality, identity crisis generated on the participants.